KLASIFIKASI PENILAIAN TERHADAP HASIL BELAJAR MAHASISWA DENGAN MENGGUNAKAN ANFIS: (Studi Kasus Mata Kuliah Matematika dan Aljabar Linear & Matrik) - Adi Candra Kusuma (Universitas Pancasakti Tegal, 2019)
Determination of the level of student learning abilities based on the results of the evaluation of the learning process is the most important stage in recognizing the absorbency characteristics of each student. It appears in the response response of the learning process from the lecturers that there is a slow and fast response, so that there needs to be a different action from the lecturer on this matter. The purpose of this study was to determine the classification of assessments of student learning outcomes by using anfis. The study was conducted in class C and E Academic Year 2017/2018 with mathematics and linear & Matrix algebra courses. Type of Quantitative Research using data collection techniques such as interviews, observations, literature studies and documentation. The data taken was tested for normality and homogeneity. The Fuzzy Sugena research results are very suitable for this classification compared to fuzzy mamdani although with fuzzy mamdani there is a smaller error rate of 0.87. Students can be categorized as very good categories of 9 students and a good category of 21 students out of a total of 30 students or can be held very well (30%), and good (70%). After the teaching staff is able to classify students based on the criteria, from that it causes the teaching staff to be able to provide feedback to all students in their class differently. The instructor is able to develop strategies in learning so that what is desired by students who have different criteria can get appropriate treatment Because an educator must be able to understand students who have a diversity of characters that cannot be compared to the way they learn